CH3NH3PbBr3–CH3NH3PbI3 Perovskite–Perovskite Tandem Solar Cells with Exceeding 2.2 V Open Circuit Voltage. Issue 25 (27th October 2015) - Heo, Jin Hyuck; Im, Sang Hyuk
Abstract : Perovskite–perovskite tandem solar cells with open‐circuit voltages of over 2.2 V are reported. These cost‐effective, solution‐processible perovskite hybrid tandem solar cells with high open‐circuit voltages are fabricated by the simple lamination of a front planar MAPbBr3 perovskite cell and a back MAPbI3 planar perovskite solar cell.